Highly anisotropic etching of Ta thin films using high density plasmas of halogen based gases. (November 2016) - Choi, Ji Hyun; Hwang, Su Min; Lee, Jai Yong; Garay, Adrian Adalberto; Chung, Chee Won
Abstract: Inductively coupled plasma reactive ion etching of Ta thin films masked with photoresist was performed using C2 F6 /Ar, HBr/Ar and Cl2 /Ar gases. The etch characteristics such as etch rate, etch selectivity and etch profile were investigated in different gas concentrations of each gas. The Cl2 chemistry showed high degree of anisotropy in etch profile as well as fastest etch rate and highest etch selectivity of Ta films among these gases. Optical emission spectroscopy revealed that the increase in chlorine radicals with increasing Cl2 concentration was responsible for the increase in the Ta etch rate. The etch rate of Ta films increased with increasing ICP rf power and dc-bias voltage, and decreasing process pressure. Good etch profiles were obtained at high rf power and dc-bias voltage, and low process pressure. X-ray photoelectron spectroscopy confirmed the existence of a chemical reaction of Ta with chlorine radicals by forming tantalum chlorides. These results suggested that Ta etching in Cl2 /Ar follows the typical reactive ion etching mechanism. It was concluded that a high degree of anisotropy and high etch rate of Ta films were achieved using Cl2 /Ar gas. Highlights: ICPRIE of Ta thin films was investigated using C2 F6 /Ar, HBr/Ar, Cl2 /Ar gases. Reactive ion etching was the dominant etch mechanism in all gas mixtures. Fast etch rate and high degree of anisotropy were achieved under Cl2 /Ar gas mixture. XPS analysis revealed the formation of tantalum chlorides on the film surface.